2021
DOI: 10.3389/fcvm.2021.725079
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Treatment of Access Site Complications During Transfemoral TAVI: A Single Center Experience

Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) has rapidly developed over the last decade and is nowadays the treatment of choice in the elderly patients irrespective of surgical risk. The outcome of these patients is mainly determined not only by the interventional procedure itself, but also by its complications.Material and Methods: We analyzed the outcome and procedural events of transfemoral TAVI procedures performed per year at our institution. The mean age of these patients is 79.2 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Additionally, our study showed that the average EIA diameter was approximately 0.5 mm smaller than the CFA diameter; insertion of large-diameter sheaths may have caused EIA injuries as well. Although CFA dissection may be treated endovascularly ( 20 ), all CFA dissections in our study required surgical repair because balloon dilation failed to improve the associated stenosis. CFA stenosis is frequently caused by tight ligation of the closure device or purse-string suture ( 20 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, our study showed that the average EIA diameter was approximately 0.5 mm smaller than the CFA diameter; insertion of large-diameter sheaths may have caused EIA injuries as well. Although CFA dissection may be treated endovascularly ( 20 ), all CFA dissections in our study required surgical repair because balloon dilation failed to improve the associated stenosis. CFA stenosis is frequently caused by tight ligation of the closure device or purse-string suture ( 20 ).…”
Section: Discussionmentioning
confidence: 95%
“…Although CFA dissection may be treated endovascularly ( 20 ), all CFA dissections in our study required surgical repair because balloon dilation failed to improve the associated stenosis. CFA stenosis is frequently caused by tight ligation of the closure device or purse-string suture ( 20 ). In the inguinal region, surgical repair is generally preferable because hip flexion may cause occlusion of an endovascular stent.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prompt and efficient diagnoses and management are necessary for achieving bleeding control, which is usually carried out via crossover angiography from the contralateral femoral artery or, more recently, from the radial artery. Limited dissection or perforation can usually be managed with prolonged occlusive balloon inflation, whereas percutaneous deployment of a stent, thrombin injection or surgical repair can be used in cases with more extensive, flow-limiting dissection or bleeding, or in cases with hemodynamic instability or threatened limb circulation [30].…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…Percutaneous deployment of a covered stent or surgical repair is indicated for more extensive flow-limiting dissection or bleeding or in cases with hemodynamic instability or threatened limb circulation. Both options are associated with good outcomes, but the percutaneous option is usually preferred over surgical repair, especially when the injury is above the inguinal ligament as the latter might require laparotomy and TAVI patients are usually old, frail, and have high perioperative risk ( 80 , 95 , 96 ).…”
Section: Transcatheter Aortic Valve Implantation and Pertinent Advers...mentioning
confidence: 99%